2016
DOI: 10.1103/physrevb.94.165203
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the band-gap energy in BiTeI

Abstract: The evolution of the electronic structure of BiTeI, a layered semiconductor with a van der Waals gap, under compression is studied by employing semilocal and dispersion-corrected density-functional calculations. Comparative analysis of the results of these calculations shows that the band-gap energy of BiTeI decreases till it attains a minimum value of zero at a critical pressure, after which it increases again. The critical pressure corresponding to the closure of the band gap is calculated, at which BiTeI be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…5,7,8 This pressure-induced band inversion is reminiscent of the behaviour of some topological insulators. [25][26][27] According to the literature, the conductivity of Pt(dmg) 2 exhibits a similar behaviour to Pt(bqd) 2 under the application of pressure, however the insulator-to-metal transition occurs at much higher pressure (5 GPa). 5 To investigate the effect of pressure on the electronic structure of Pt(dmg) 2 we calculated the band structure, PDOS and -COHP PtÁ Á ÁPt interaction at 3.14 GPa (Fig.…”
Section: High Pressure Conductivitymentioning
confidence: 89%
“…5,7,8 This pressure-induced band inversion is reminiscent of the behaviour of some topological insulators. [25][26][27] According to the literature, the conductivity of Pt(dmg) 2 exhibits a similar behaviour to Pt(bqd) 2 under the application of pressure, however the insulator-to-metal transition occurs at much higher pressure (5 GPa). 5 To investigate the effect of pressure on the electronic structure of Pt(dmg) 2 we calculated the band structure, PDOS and -COHP PtÁ Á ÁPt interaction at 3.14 GPa (Fig.…”
Section: High Pressure Conductivitymentioning
confidence: 89%
“…Detailed ab initio studies of ∆ can be found in Ref. [35,36]. While the underestimation of the gap in semiconductors is a well-known feature of semilocal functionals, the fact that the description of the gap is better when the p 1/2 states are not included may be associated with a fortuitous cancelation of errors.…”
Section: Methodological Aspects Of the Density Functional Theory Calcmentioning
confidence: 99%
“…Hacim oranı ⁄ 0 değiştikçe hem bant aralık enerjisi hem de bantların şekli (dispersiyonu) değişim göstermektedir. Bant aralığı enerjisinin basınç ile gösterdiği değişim önceki bir yayınımızda [10]…”
Section: Bulgular Ve Tartışmaunclassified
“…Rashba tipi yarılmalar yarıiletken elektronlarının spin polarizasyonunun harici elektrik alanlarla kontrol edilmesine olanak sağladığı [2, 3] için BiTeI'nin spintronik cihazlarda kullanımı cazip görülmektedir. BiTeI basınç altında topolojik faz geçişi göstermesi [4][5][6][7][8][9][10] ve termoelektrik özellikleri [11][12][13] ile de dikkat toplamaktadır.…”
Section: Introductionunclassified